2004
DOI: 10.1080/14992020400050039
|View full text |Cite
|
Sign up to set email alerts
|

Presbyacusis—hearing thresholds and the ISO 7029

Abstract: The purpose of this study was to analyse the changes in pure-tone hearing thresholds with age. We studied a random sample of 232 elderly subjects with a battery of audiological tests, including pure-tone audiometry in the conventional and extended high-frequency range, using the normative distributions from the International Organization for Standardization (ISO) standard 7029 for comparison. Sixty otologically normal (ON) subjects were selected for comparative analysis with the unscreened (US) sample, and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 15 publications
3
30
0
5
Order By: Relevance
“…It is therefore reasonable to suggest that although presbycusis affects the high frequency sounds at the outset, the hearing loss extends to the lower frequencies with time resulting in poor speech detection as well as poor speech understanding 22 . On the contrary some studies had found that the lower (including the speech frequencies) were relatively preserved in age-related hearing loss 23,24 .These may be a result of variations in the study populations as many of such studies focused mainly on elderly individuals with hearing impairment and not necessarily presbycusis. Differences in the genetic constitutions of the various populations could also play a part in the factors.…”
Section: Discussionmentioning
confidence: 77%
“…It is therefore reasonable to suggest that although presbycusis affects the high frequency sounds at the outset, the hearing loss extends to the lower frequencies with time resulting in poor speech detection as well as poor speech understanding 22 . On the contrary some studies had found that the lower (including the speech frequencies) were relatively preserved in age-related hearing loss 23,24 .These may be a result of variations in the study populations as many of such studies focused mainly on elderly individuals with hearing impairment and not necessarily presbycusis. Differences in the genetic constitutions of the various populations could also play a part in the factors.…”
Section: Discussionmentioning
confidence: 77%
“…The dip at 4 kHz seen in the male curve is smaller in the present study than that in the corresponding ISO 7029 (2000) standard. Stenklev and Laukli (2004) found the dip at 4 kHz to be relatively smaller, as well. Also Pearson et al (1995) reported better thresholds at 3 to 8 kHz for men compared to ISO 7029 (2000).…”
Section: Comparison With Iso 7029mentioning
confidence: 89%
“…The majority of authors used the mean as the central measure (Stelmachowicz et al, 1989a;Schechter et al, 1986;Levina et al, 2003;Lee et al, 2012e;Sakamoto et al, 1998;Allen and Eddins, 2010;Hannula et al, 2011;Shim et al, 2009). Stenklev and Laukli (2004) used the median, while some authors calculated both mean and median (Wiley et al, 1998;Ahmed et al, 2001).…”
Section: A Median and Meanmentioning
confidence: 99%
See 1 more Smart Citation
“…As a polycausal chronic disease it is difficult to define hearing loss in the elderly as a decline in auditory sensitivity caused only by age-related degeneration. 6,20 Rosenhall 18 has suggested the term age-related hearing loss as an alternative expression for presbyacusis, due to a general difficulty in audiological research and practice of defining hearing loss as purely the consequence of natural aging (which could be named pure presbyacusis).…”
Section: Introductionmentioning
confidence: 99%